2021
DOI: 10.3389/fpsyg.2021.670959
|View full text |Cite
|
Sign up to set email alerts
|

Paranormal Belief, Thinking Style and Delusion Formation: A Latent Profile Analysis of Within-Individual Variations in Experience-Based Paranormal Facets

Abstract: This study examined the degree to which within-individual variations in paranormal experience were related to belief in the paranormal, preferential thinking style, and delusion formation. A sample of 956 non-clinical adults completed measures assessing experience-based paranormal indices (i.e., paranormal experience, paranormal practitioner visiting, and paranormal ability), paranormal belief, belief in science, proneness to reality testing deficits, and emotion-based reasoning. Latent profile analysis (LPA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 91 publications
1
28
1
Order By: Relevance
“… Drinkwater et al (2021b) found that greater personal involvement with the paranormal (i.e., experience, visiting practitioners and self-professed ability) was associated with increased proneness to reality testing deficits, greater emotion-based reasoning, and higher paranormal belief. These results deepened conceptual understanding by demonstrating that nuanced variations in paranormal experience were related to subtle differences in cognitive-perceptual factors allied to subclinical delusion formation and thinking style.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“… Drinkwater et al (2021b) found that greater personal involvement with the paranormal (i.e., experience, visiting practitioners and self-professed ability) was associated with increased proneness to reality testing deficits, greater emotion-based reasoning, and higher paranormal belief. These results deepened conceptual understanding by demonstrating that nuanced variations in paranormal experience were related to subtle differences in cognitive-perceptual factors allied to subclinical delusion formation and thinking style.…”
Section: Introductionmentioning
confidence: 95%
“…Respondents indicated whether they had visited each practitioner type using a dichotomous format (yes vs. no). This scale has demonstrated satisfactory internal reliability (Drinkwater et al, 2021b). Scores thus ranged from 0 to 4, with higher scores indicating greater interaction with paranormal practitioners.…”
Section: Practitioner Visitingmentioning
confidence: 99%
See 2 more Smart Citations
“…Noting these factors, Drinkwater et al (2021a , b) used self-professed paranormal ability as an index of experience. Although researchers have under investigated the role of facility, measurement instruments have historically recognised the importance and independence of ability, belief and experience.…”
Section: Introductionmentioning
confidence: 99%